Isolated hepatic tuberculosis in a middle aged diabetic lady: a rare case report - Hasan, Md Mehedi; Islam, Mohammad Tajul; Haque, Hasna Fahmima; Ahmed, AKM Shaheen (BIRDEM Medical Journal, 2023)
Isolated hepatic tuberculosis is a rare clinical entity with non-specific clinical and imaging features that can result in a diagnostic challenge. A high index of suspicion is required and a definitive diagnosis can be very difficult. Here, we report a case of a 55-year-old Bangladeshi lady with type 2 diabetes mellitus and hypertension presenting with prolonged fever and tender hepatomegaly. After initial evaluation she was found to have raised alkaline phosphatase and γ-glutamyl transferase levels. A diagnosis of hepatic tuberculosis was confirmed from histopathology of liver tissue. Anti-tuberculosis therapy was started. Although rare, hepatic tuberculosis should be considered in any case of unexplained hepatomegaly or hepatosplenomegaly with prolonged fever. A liver biopsy should be performed, as this condition responds well to anti-tuberculosis therapy. BIRDEM Med J 2023; 13(3): 155-159